Banks' financial distress, lending supply and consumption expenditure - H. Evren Damar; Reint E. Gropp; Adi Mordel (Goethe University Frankfurt, SAFE - Sustainable Architecture for Finance in Europe, 2014)
We employ a unique identification strategy linking survey data on household consumption expenditure to bank-level data to estimate the effects of bank financial distress on consumer credit and consump- tion expenditures. We show that households whose banks were more exposed to funding shocks report lower levels of non-mortgage liabilities. This, however, does not result in lower levels of consumption. Households compensate by drawing down liquid assets to smooth consumption in the face of a temporary adverse lending supply shock. The results contrast with recent evidence on the real effects of finance on firms' investment and employment decisions.
Keywords: E21; E44; G21; G01; 330; Credit supply; banking; financial crisis; consumption expenditure; liquid assets; consumption smoothing